Disease Pattern in Women of Mountain Area “A Study of Women Attending Gynaecological Health Camp at District Hospital, Jumla” - Pantha, Sandesh; Gartoulla, P (Journal of General Practice and Emergency Medicine of Nepal, 2010)
Introduction: The study aims in finding out the basic reproductive health condition of the women in rural areas of Nepal who are lacking far behind in access to basic health facilities and to fill in the gap of the evidence present in these areas. Methods: This study is the descriptive analysis of women who attended the 10 day long gynaecological Health camp organized at the premises of District Hospital, Jumla during October 2008, led by a Gynaecologist from Kathmandu. The diagnosis was made on clinical evaluation. A carbon copy of the prescription was made at the time of examination and was later analysed using Epi Info 4.3.3. Results: 565 of 640 women had attended the camp were included in the study. Majority of them were suffering from RTI, followed by infertility and pelvic organ prolapse. Most of them had adopted the permanent methods for family planning and the average family size for adopting permanent method was 2.9 Conclusion: Major Reproductive Health (RH) morbidity in the study was Pelvic Inflammatory Disease (PID), cervicitis and vaginitis. A significant number of the women were suffering from urinary tract infection, acid peptic disorder. Drugs as per protocol for STI treatment was most frequently used while ranitidine was the most common drug besides antibiotics. Most of them adopted vasectomy as the method of family planning, showing the increasing trend for awareness about family planning.